2010
DOI: 10.1007/s10903-010-9399-4
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Iraqi Immigrant Women in Metro Detroit: A Pilot Study

Abstract: Violence against women is an important public health problem. The objective of this study was to examine the prevalence of intimate partner violence (IPV) among immigrant Iraqi women, and to explore the association between IPV and self-rated health. A pilot study using a previously published, self-report questionnaire was carried out among a convenience sampling of 55 Iraqi women in greater Detroit. The overall prevalence of controlling behavior, threatening behavior, and physical violence was 93, 76, and 80%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…A study from the United Kingdom, for example, found that women with insecure immigration status were more vulnerable to intensified domestic violence. 5 Another study documented a high prevalence of intimate partner violence (IPV) among immigrant Iraqi women in the United States 6 and their poor self-rated health. More research about migrant women who have experienced violence related to pregnancy, 7 particularly in industrialized countries, would advance the knowledge base on GBV in migrants.…”
Section: Introductionmentioning
confidence: 99%
“…A study from the United Kingdom, for example, found that women with insecure immigration status were more vulnerable to intensified domestic violence. 5 Another study documented a high prevalence of intimate partner violence (IPV) among immigrant Iraqi women in the United States 6 and their poor self-rated health. More research about migrant women who have experienced violence related to pregnancy, 7 particularly in industrialized countries, would advance the knowledge base on GBV in migrants.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, immigrant couples coming from majority-Muslim countries show higher IPV rates if compared to their non-immigrant counterparts: for example, Moroccan immigrant women in Spain (Colorado-Yohar et al, 2012), Iraqi (Barkho, Fakhouri, & Arnetz, 2011), as well as Pakistani and South-Asian (Adam & Schewe, 2007; Lee & Hadeed, 2009) women immigrated to the U.S. report being exposed to abusive behaviors to a greater extend if compared to the native population and even to other non-immigrant Muslim women.…”
mentioning
confidence: 99%
“…Also, the study showed an association between exposure to IPV and suicide attempts, which is supported by previous research (5, 15). Exposure to IPV is also related to poor mental health among foreign-born women more generally (17, 18). …”
mentioning
confidence: 99%